Marine bacteriophages disturb the associated microbiota of Aurelia aurita with a recoverable effect on host morphology - Stante, Melissa; Weiland-Bräuer, Nancy; von Hoyningen-Huene, Avril Jean Elisabeth; Schmitz, Ruth Anne (Frontiers in Microbiology, 2024)
The concept of the metaorganism describes a multicellular host and its diverse microbial community, which form one biological unit with a combined genetic repertoire that significantly influences health and survival of the host. The present study delved into the emerging field of bacteriophage research within metaorganisms, focusing on the moon jellyfish Aurelia aurita as a model organism. The previously isolated Pseudomonas phage BSwM KMM1 and Citrobacter phages BSwM KMM2 -KMM4 demonstrated potent infectivity on bacteria present in the A. aurita-associated microbiota. In a host-fitness experiment, Baltic Sea subpopulation polyps were exposed to individual phages and a phage cocktail, monitoring polyp survival and morphology, as well as microbiome changes. The following effects were obtained. First, phage exposure in general led to recoverable malformations in polyps without affecting their survival. Second, analyses of the community structure, using 16S rRNA amplicon sequencing, revealed alterations in the associated microbial community in response to phage exposure. Third, the native microbiota is dominated by an uncultured likely novel Mycoplasma species, potentially specific to A. aurita. Notably, this main colonizer showed resilience through the recovery after initial declines, which aligned with abundance changes in Bacteroidota and Proteobacteria, suggesting a dynamic and adaptable microbial community. Overall, this study demonstrates the resilience of the A. aurita metaorganism facing phage-induced perturbations, emphasizing the importance of understanding host-phage interactions in metaorganism biology. These findings have implications for ecological adaptation and conservation in the rapidly changing marine environment, particularly regarding the regulation of blooming species and the health of marine ecosystems during ongoing environmental changes.